Piezoresistive Effect: A New Concept for Hearing Aids - Mengyao Gao; Weijie Liu; Kun Chen; Huili Sun; Xiaoqing Liu; Haonan Xing; Huatang Wang; Benpeng Zhu; Haizhong Guo (Advanced Science)
Abstract Hearing loss is among the most prevalent sensory impairments globally. Hearing aids assist individuals with hearing impairments in perceiving sound more effectively, serving as essential tools for reconnecting them with the world. Herein, an MXene/Polyvinyl Alcohol sound sensor (MPSS) capable of recognizing weak sound signals is developed. It can not only recognize different speech signals and sound properties but also show good stability in the process of long‐term sound recording. In addition, by combining the sensor with machine learning, the accuracy rate of voiceprint recognition of wildlife conservation is up to 99%, underscoring its practical significance for wildlife protection. Utilizing piezoresistive effects, a hearing aid with a detection sound threshold of 60 dB and a frequency range of 20–4000 Hz is achieved, which provides a feasible scheme in hearing aids.